2010
DOI: 10.1016/j.jeconom.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge spillovers in US patents: A dynamic patent intensity model with secret common innovation factors

Abstract: During the past two decades, innovations protected by patents have played a key role in business strategies. This fact enhanced studies of the determinants of patents and the impact of patents on innovation and competitive advantage. Sustaining competitive advantages is as important as creating them. Patents help sustaining competivite advantages by increasing the production cost of competitors, by signaling a better quality of products and by serving as barriers to entry. If patents are rewards for innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The response in patents may be delayed by lags between investment and patenting. The patents literature has generally found a economically and statistically strong contemporaneous effect (Blazsek and Escribano, 2010;Gurmu and Perez-Sebastian, 2008;Hall et al, 1986;Montalvo, 1997); an exception is Blundell et al (2002) who find a slower effect under additional modelling assumptions.…”
Section: Solutionmentioning
confidence: 98%
“…The response in patents may be delayed by lags between investment and patenting. The patents literature has generally found a economically and statistically strong contemporaneous effect (Blazsek and Escribano, 2010;Gurmu and Perez-Sebastian, 2008;Hall et al, 1986;Montalvo, 1997); an exception is Blundell et al (2002) who find a slower effect under additional modelling assumptions.…”
Section: Solutionmentioning
confidence: 98%
“…As we will see, this implies that the expected licensing revenue from owning a patent does not 8 Empirical analyses of patent citations provide direct empirical support for the presence of such inter-industry patent overlap. Fung (2005) and Blazsek and Escribano (2010) document that newly granted patents routinely include citations of existing patents across different industries, and such inter-industry citations often comprise the majority of a patent's total citations. In addition, Niwa (2016Niwa ( , 2018 analyze licensing agreements across industries in the context of horizontal innovation in a variety expansion model of growth.…”
Section: Patents Versus Secrecymentioning
confidence: 99%
“…Blazsek et. al., (2010) suggested that patents' higher requirements for output quality and service will form entry barriers to competitors, and increase their production cost so as to maintain the sustainable competitive advantage of manufacturing [42]. The quality of patent output depends on optimal allocation of a variety of resources, and different resource allocation will form different green process innovation path.…”
Section: The Ecorole Attribute Of Green Process Innovationmentioning
confidence: 99%